SGA Children in Pediatric Primary Care - Patrizia Gallo MD (Global Pediatric Health, 2016)
Background: Epidemiologic evidences suggest a strong association between low birth weight and some diseases in adult life ( hypertension, diabetes, cardiovascular diseases).Aim of this study was to evaluate the obesity/overweight prevalence in a population of children born small for gestation age, SGA children 400, 208 males and 192 females compared to a population of children born appropriate for gestational age 6818 AGA children, 3502 males and 3316 females, during childhood. Our intention was also to build the natural history of weight gain during prepubertal age in children born SGA and AGA. Design and Methods: Observational prospective longitudinal study. We followed our patients from January2001 up to December 2010; weight, height and body mass index (BMI) were evaluated in all the SGA and AGA children. BMI z -score range for defining overweight and obesity was, respectively, 1.13 to 1.7 and >1.7 according to CDC growth charts. Results: In transversal evaluation , we prove that 10-year-old SGA females are twice obese and more overweight compared to equal age AGA females. In longitudinal evaluation , we highlight different observations: SGA children obese at 2 years are still obese at 10 years; the number of obese SGA children increases gradually until the age of 10; AGA children, appear to be less obese than SGA children at 10 years. Conclusion: SGA males and females are more obese at 5 and 10 years compared to the AGA population. Primary care pediatricians, through early detection of the children at risk, can carry out an effective obesity prevention project in SGA children.